Proceedings. International Symposium on Advanced Packaging Materials: Processes, Properties and Interfaces, 2005.
DOI: 10.1109/isapm.2005.1432043
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive modeling of lead-free solders

Abstract: Solders are used extensively as electrical interconnects in microelectronics packaging. Because of environmental concerns, lead-based solders are being replaced by Sn/Ag and Sn/Ag/Cu based solder materials.Since the thermomechanical reliability of modern electronic devices depends on, to a large extent, the fatigue and creep behavior of the solder joints, it is imperative to understand the deformation behavior of these new lead-free solders. This study conducted extensive thermomechanical testing on several co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Pang [8] has shown that young's modulus and yield stress of Sn-Pb are highly depended on strain rate and temperature. Pei [9] executed tensile tests over a wide range of temperatures and low strain rates (10-S 10-3 10-1 per sec) with two types of lead free materials (96.SSn3.SAg and 9S.SSn3.8AgO.7Cu). Although a large numbers of researchers focus on low strain rates, the constitution models of those materials at high strain rates are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Pang [8] has shown that young's modulus and yield stress of Sn-Pb are highly depended on strain rate and temperature. Pei [9] executed tensile tests over a wide range of temperatures and low strain rates (10-S 10-3 10-1 per sec) with two types of lead free materials (96.SSn3.SAg and 9S.SSn3.8AgO.7Cu). Although a large numbers of researchers focus on low strain rates, the constitution models of those materials at high strain rates are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Pei and coworkers [27] have calculated the nine parameters of the Anand model by conducting tensile testing of Sn3.5Ag and Sn3.8Ag0.7Cu lead free solders at several temperatures and strain rates.…”
Section: Introductionmentioning
confidence: 99%
“…A FOR-TRAN subroutine, calculating the stress increment and material Jacobian matrix, knowing the strain field, was written. Simulations and verifications with various solders revealed that there are good agreements between the user subroutine and bibliography results presented in [16,17]. Table 4 lists hereafter the two solders constitutive laws parameters.…”
Section: Solders Jointsmentioning
confidence: 66%